(untitled) (Journal of Mathematical Study, 2025)
In this paper, we show that a smooth 4-manifold diffeomorphic to a complex hypersurface in CP^3 of degree d≥5 can be decomposed as the union of d(d−4)^2 copies of 4-dimensional pair-of-pants and certain subsets of K3 surfaces.